Adsorption of Amido Black 10B from Aqueous Solution Using Weed Waste as Adsorbent: Characterization, Equilibrium, Kinetic and Thermodynamic Studies - Kaur, Rajvir; Kaur, Harpreet (Asian Journal of Chemistry, 2016)
In the present work, Calotropis procera leaf powder has been studied to assess its capacity for the adsorption of hazardous dye Amido black 10B from aqueous solution. The adsorbent has been characterized by scanning electron microscopy and Fourier transformer infrared spectrometer. The influence of various experimental parameters such as contact time, initial dye concentrations, adsorbent dosage, ionic strength, temperature and pH of dye solution has been studied. The adsorption process represented with Langmuir, Freundlich, Tempkin and Dubinin-Radushkevich isotherms. The maximum adsorption capacity of Amido black 10B onto adsorbent was 19.31 mg g-1. Pseudo second order kinetics has been best fitted, with high correlation coefficients. The calculated values of thermodynamic parameters such as DH° and DS° for uptake of dye have been found to be 26.8811 kJ mol–1 and 78.5697 J mol–1 K–1, respectively.